Research on the application of thermal field emission gun in electron beam lithography - Hao Xiaoliang; Zhao Yingwei; Sun Hu; Wang Xiuhai; Cao Jian; Ma Peisheng; Ren Zesheng (Dianzi Jishu Yingyong, 2022)
The classification and characteristics of electron gun are introduced, with emphasis on the principle, structure and characteristics of thermal field emission gun and its application in electron beam lithography machine. The relationship between the beam current of the electron beam lithography machine and the extractor current of the electron gun is described, and the influence of the parameters of the thermal field emission gun on the extractor current is analyzed. The influence of the adjustment of the thermal field emission gun on the electron beam lithography process is studied, and the relationship between the beam spot and the beam current is obtained through experiments. Finally, by adjusting the parameters of the electron gun, different lithography patterns are prepared to meet the requirements of different lithography processes, and the conclusions of the analysis are verified.